1987
DOI: 10.1128/mcb.7.7.2644
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional inactivation of c-myc and the transferrin receptor in dibutyryl cyclic AMP-treated HL-60 cells.

Abstract: Treatment of HL-60 cells with dibutyryl cyclic AMP induced rapid transcriptional inactivation of c-myc and the transferrin receptor. Transcriptional inactivation was followed by loss of c-myc and transferrin receptor mRNA and protein. Treated cells completed one round of proliferation, followed by growth arrest, G1 synchronization, and monocytic differentiation. These data suggest that cyclic AMP-mediated control of growth and differentiation may be achieved, at least in part, by transcriptional regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 28 publications
3
19
1
Order By: Relevance
“…The p38 pathway also plays an essential role in regulating many cellular processes including inflammation, cell differentiation, cell cycle, cell growth and death [12] . Regarding the effect of cAMP on the cell cycle progression, several reports demonstrated that cAMP could induce G1 synchronization, growth arrest, and terminal differentiation in certain cells [13,14] . For example, Lee et al [15] , showed that cAMP could induce G1 arrest and apoptosis in hepatoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…The p38 pathway also plays an essential role in regulating many cellular processes including inflammation, cell differentiation, cell cycle, cell growth and death [12] . Regarding the effect of cAMP on the cell cycle progression, several reports demonstrated that cAMP could induce G1 synchronization, growth arrest, and terminal differentiation in certain cells [13,14] . For example, Lee et al [15] , showed that cAMP could induce G1 arrest and apoptosis in hepatoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…We also achieved growth arrest conditions by inducing the differentiation of HL60 cells. Exposure to Bu2AMP or TPA has been shown to induce terminal monocytic differentiation of this promyelocytic cell line (22 with Bu2AMP induced morphologic chat of differentiation, cessation of cell grow decrease in DNA synthesis but induced n or A45 RNA (Fig. 4).…”
mentioning
confidence: 99%
“…A major RNA cap site was mapped by primer extension downstream of the GC-rich stretch with several consensus sites for the transcription factor SPl, including SPl sites, which partly overlapped the consensus sites for the GC factor, reported to repress transcriptional activation of the EGF receptor gene [22]. Proximal to that cluster, an AP2 site, previously described as responsive to CAMP and TPA [23,24], was located. The promoter proximal part conferred maximal activity in a transient transfection assay.…”
Section: Discussionmentioning
confidence: 99%
“…None of these cell lines express detectable amounts of RNA St. The transfected cells were then stimulated with TPA, 24], or dexamethasone [25]. All three compounds elicited minor or no detectable effects compared to the untreated control (data not shown).…”
Section: Deletional Analysis Of the Plc?$ Promotermentioning
confidence: 99%